TAIWAN’S OVERALL DEFENCE CONCEPT MILITARY POSTURE: A SECURITIZATION THEORY ANALYSIS - Muhammad Erza Aimar Rizky; Muhammad Reza Iskandar Salim (Indonesian Association for International Relations, 2025)
The entrance of President Tsai Ing-Wen’s party, the DPP, into power marked a shift in Taiwan’s attitude towards China. This comes as a response to China’s increasingly threatening rhetoric and incursion on Taiwan’s de facto sovereignty in the latter half of the 2010s. Taiwan’s military chief during Tsai’s presidency, Admiral Lee Hsi-Min, introduced the Overall Defense Concept (ODC) during his tenure as the basis for reform in the armed forces posture. The introduction of ODC signals the acceptance of Taiwan’s military establishment on China as the primary existential threat. We analyzed the securitizing process with a version of securitization theory from Thierry Balzacq. To operationalize this theory, this paper will use a qualitative approach using literature study. We hypothesize that the change in Taiwan’s security officials' perception towards China and the adoption of ODC is caused by the increasingly aggressive approach by Beijing towards Taipei.